Integration of accessibility design patterns with the software implementation process of ISO/IEC 29110. Issue 1 (10th August 2018) - Sanchez‐Gordon, Sandra; Sánchez‐Gordón, Mary; Yilmaz, Murat; O'Connor, Rory V.
Abstract: The Web Content Accessibility Guidelines was developed by World Wide Web Consortium with a goal of providing a single shared standard for web content accessibility that meets the needs of individuals, organizations, and governments. Given that there is a large percentage of very small entities that develop software who also utilize the ISO/IEC software process standard, the purpose of this study is the development of software design patterns for users with visual disabilities. As a result, four accessibility design patterns are defined: Authentication adapter, Blindness adapter, Dichromatic color vision adapter, and Blurry vision adapter. These patterns will help to improve the design of the web applications built using them while being compliant with the ISO/IEC 29110 standard. The use of design patterns also enables the transfer of design experience to programming practices and improves the software documentation. To validate the set of patterns, an online course for Spanish speakers was developed, and the evaluation was carried out using simulators, automated tools, experts, and users. Simulators and automated tools showed no accessibility errors and experts evaluated 10 heuristics principles and did not identify any severity issues. Taken together, our results provide positive evidence that users with visual disabilities could benefit from the proposed features. Abstract : In this study, we introduce design patterns within the software implementation process of ISO/IEC 29110 to guarantee a good level of accessibility in the products built using this standard. The accessibility design patterns defined in this proposal are an authentication adapter and three adapters for three types of visual disabilities: blindness, dichromatic color vision, and blurry vision. The evaluation of the web application was carried out using simulators, automated tools, experts, and users resulting in no accessibility errors.